Mapping the structural, magnetic and electronic behavior of (Eu1−xCax)2Ir2O7 across a metal–insulator transition. (5th November 2020) - Zoghlin, Eli; Porter, Zach; Britner, Samuel; Husremovic, Samra; Choi, Yongseong; Haskel, Daniel; Laurita, Geneva; Wilson, Stephen D
Abstract: In this study, we employ bulk electronic properties characterization and x-ray scattering/spectroscopy techniques to map the structural, magnetic and electronic properties of (Eu1− x Ca x )2 Ir2 O7 as a function of Ca-doping. As expected, the metal-insulator transition temperature, T MIT, decreases with Ca-doping until a metallic state is realized down to 2 K. In contrast, T AFM becomes decoupled from the MIT and (likely short-range) AFM order persists into the metallic regime. This decoupling is understood as a result of the onset of an electronically phase separated state, the occurrence of which seemingly depends on both synthesis method and rare earth site magnetism. PDF analysis suggests that electronic phase separation occurs without accompanying chemical phase segregation or changes in the short-range crystallographic symmetry while synchrotron x-ray diffraction confirms that there is no change in the long-range crystallographic symmetry. X-ray absorption measurements confirm the J eff = ½ character of (Eu1− x Ca x )2 Ir2 O7 . Surprisingly these measurements also indicate a net electron doping, rather than the expected hole doping, indicating a compensatory mechanism. Lastly, XMCD measurements show a weak Ir magnetic polarization that is largely unaffected by Ca-doping. Keywords: term, term, term.